L1 and HERV-W retrotransposons are hypomethylated in human ovarian carcinomas - Menendez, Laura (BioMed Central, 2004)
Wide-spread hypomethylation of CpG dinucleotides is characteristic of many cancers. Retrotransposons have been identified as potential targets of hypomethylation during cellular transformation. We report the results of an preliminary examination of the methylation status of CpG dinucleotides associated with the L1 and HERV-W retrotransposons in benign and malignant human ovarian tumors. We find a reduction in the methylation of CpG dinucleotides within the promoter regions of these retroelements in malignant relative to non-malignant ovarian tissues. Consistent with these results, we find that relative L1 and HERV-W expression levels are elevated in representative samples of malignant vs. non-malignant ovarian tissues.